2016
DOI: 10.1590/s0100-83582016340300018
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Protoporphyrinogen Oxidase Inhibitor Herbicides in Wild Poinsettia

Abstract: -Weed resistance to herbicides is a major global problem for agriculture. In recent years, the increased use of herbicides, without proper planning, has led to a large increase in the number of cases of weed biotypes that are resistant to one or more herbicide mechanism of action. Wild poinsettia biotypes (Euphorbia heterophylla), discovered in the State of Paraná, with resistance to herbicides that inhibit protoporphyrinogen oxidase (PROTOX) and acetolactate synthase (ALS), are the first case to exhibit multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Mutations in the same amino acid position were previously found in A. artemisiifolia and A. palmeri resistant to PPO inhibitors (Giacomini et al 2017;Sarangi et al 2019). Inheritance studies conducted with other E. heterophylla populations showed a single nuclear and dominant gene involved with PPO-inhibitor resistance (Brusamarello et al 2016). A single and dominant resistance allele supports our results for a target-site mutation as the only mechanism of resistance.…”
Section: Weed Sciencesupporting
confidence: 89%
“…Mutations in the same amino acid position were previously found in A. artemisiifolia and A. palmeri resistant to PPO inhibitors (Giacomini et al 2017;Sarangi et al 2019). Inheritance studies conducted with other E. heterophylla populations showed a single nuclear and dominant gene involved with PPO-inhibitor resistance (Brusamarello et al 2016). A single and dominant resistance allele supports our results for a target-site mutation as the only mechanism of resistance.…”
Section: Weed Sciencesupporting
confidence: 89%
“…As is the case with A. tuberculatus, PPO-inhibitor resistance in E. heterophylla exhibits broad cross-resistance and is conferred by a single, (partially) dominant, nuclear gene. 33,34 Trezzi et al suggested that resistance could be attributable to differential leaf absorption, but this has yet to be confirmed. 35 There are at least a couple of cases in which resistance to PPO inhibitors probably occurred as a result of selection by herbicides with different target sites.…”
Section: Use Of Ppo Herbicidesmentioning
confidence: 99%
“…Additionally, some mechanistic work has been reported for Euphorbia heterophylla , the second weed species identified with resistance to PPO inhibitors (Table ). As is the case with A. tuberculatus , PPO‐inhibitor resistance in E. heterophylla exhibits broad cross‐resistance and is conferred by a single, (partially) dominant, nuclear gene . Trezzi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Fenoxaprop-P-ethyl is a herbicide inhibitor of the enzyme acetyl-coenzyme, a carboxylase (ACCase inhibitor) that acts in the postemergence control of grasses (Takano et al, 2020). Clomazone is a synthase inhibitor (DOXP inhibitor), which is a pivotal component for plastid isoprenoid synthesis (Cabral et al, 2017), whereas carfentrazone-ethyl causes the inhibition of the protoporphyrinogen oxidase enzyme (PPO inhibitor) (Brusamarello, 2016). The commercial premix of clomazone + carfentrazone-ethyl is registered for the pre-and postemergence control of grass and broadleaf weeds in several crops.…”
Section: Introductionmentioning
confidence: 99%